2021
DOI: 10.1080/20479700.2020.1870365
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable medical tourism: Investigating health-care travel in Indonesia and Malaysia

Abstract: Medical tourism has developed rapidly and international health care has become a global industry. Indonesia has a great opportunity in the field of medical tourism, but Malaysia still ranks more highly in credibility by domestic and foreign residents in checking their health. The purpose of this study is to identify potential development of medical services with the concept of medical tourism in Indonesia by comparing with Malaysia. This study uses combination of quantitative and qualitative approaches. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
(38 reference statements)
2
30
0
1
Order By: Relevance
“…This finding is well supported by the results of the study put forward by Yalcin et al (2009), which states that brand association has a significant positive effect on attitude. In line with Ratnasari et al (2020aRatnasari et al ( , 2020bRatnasari et al ( , 2020cRatnasari et al ( , 2020d, it was found that store image significantly strengthens (2003), which shows that brand associations have a very strong influence on consumer attitudes toward brands. Thus, the stronger and positive the brand association being built, the more positive the consumer's attitude toward a brand.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This finding is well supported by the results of the study put forward by Yalcin et al (2009), which states that brand association has a significant positive effect on attitude. In line with Ratnasari et al (2020aRatnasari et al ( , 2020bRatnasari et al ( , 2020cRatnasari et al ( , 2020d, it was found that store image significantly strengthens (2003), which shows that brand associations have a very strong influence on consumer attitudes toward brands. Thus, the stronger and positive the brand association being built, the more positive the consumer's attitude toward a brand.…”
Section: Discussionsupporting
confidence: 75%
“…Sedianingsih et al (2019) stated that the quality, equipment, management, price, benefit comparisons and communication affect the intention. Ratnasari et al (2020aRatnasari et al ( , 2020bRatnasari et al ( , 2020cRatnasari et al ( , 2020d) also supported that purchase intention is influenced by the brand both directly or indirectly. Purchase intentions are influenced by the brand associations, the feelings attached to a brand as well as the brand's personality were found to have stronger relationships with purchase intention.…”
Section: Brand Association and Intention To Buy Luxury Carsmentioning
confidence: 93%
“…They also revealed that medical complications and legal conditions influence medical tourists' satisfaction. Ratnasari et al (2021) compared medical services in Indonesia with Malaysia in the field of medical tourism. They showed the important factors such as trust, communication interactions, excellent service, affordable medical costs, modern medical technology, holistic service, increased patient expectations, short distances and an interest.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the age of globalization with the help of market liberalization such as insurance, increased patient mobility due to greater ease of transportation and technological development along with the participation of the private sector in health care has increased medical tourism (Ratnasari et al, 2021). At the time of globalization, medical tourism is the practice of travelling beyond national borders in order to get private medical treatment and care.…”
Section: Literature Reviewmentioning
confidence: 99%